Congestive heart failure in normotensive man. Haemodynamics, renin, and angiotensin II blockade. Issue 10 (October 1978) - Turini, G A; Brunner, H R; Ferguson, R K; Rivier, J L; Gavras, H
Abstract : The role of the renin angiotensin system was evaluated in 18 normotensive patients with chronic congestive heart failure and in 5 controls. No correlation was observed between plasma renin activity and cardiac index. There was a significant inverse correlation between renin and pulmonary capillary wedge pressure (r = -0.61, P less than 0.01). Renin values of the patients appeared to be increased when compared with controls with similar left ventricular filling pressure. Specific angiotensin II inhibition by saralasin decreased arterial pressure in 8 out of 14 patients: their renin was significantly higher than that of the remaining 6 patients (P less than 0.01). The 2 patients with the lowest renin levels responded to saralasin with a blood pressure increase. Left ventricular filling pressure decreased in all but these latter 2 patients with either little change or an increase in stroke volume. Thus, renin levels appear to be increased in normotensive patients with congestive heart failure when related to left ventricular filling pressure. Renin via angiotensin II plays a role in the blood pressure control of many patients with congestive heart failure. In some patients angiotensin II blockade appears to improve cardiac function by unloading the left ventricle.